Microwave-Assisted Improved Extraction and Purification of Anticancer Nimbolide from Azadirachta indica (Neem) Leaves - Panawan Suttiarporn; Vachira Choommongkol (Molecules, 2020)
Nimbolide, a limonoid present in leaves of the neem tree (Azadirachta indica), is an anticancer compound against a panel of human cancer cell lines. The rapid process of extraction and purification of the nimbolide from the leaves of neem tree through microwave-assisted extraction (MAE) coupled with a chromatographic technique was accomplished. The crude with a maximum content of nimbolide could be recovered from neem leaves through MAE. By using three-factors, three-level Box–Behnken design of response surface methodology (RSM), the optimal conditions for nimbolide extraction (R2 = 0.9019) were solid/liquid ratio 1:16 g/mL, microwave power 280 W, and extraction time 22 min. The enriched extract was further purified by a preparative thin-layer chromatography (PTLC), where nimbolide was obtained as 0.0336 g (0.67% yield, purity over 98%) with ethyl acetate/hexane = 4:6 in 3.0 h. Structural elucidation was performed through spectroscopic techniques, including FT-IR, 1H, and 13C-NMR. This method was simple and had a good potential for the purification of bioactive compounds from a natural product.